2008
DOI: 10.1063/1.2919131
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance–coupled fluorescence tomography scanner for molecular imaging of tissue

Abstract: A multichannel spectrally resolved optical tomography system to image molecular targets in small animals from within a clinical MRI is described. Long source/detector fibers operate in contact mode and couple light from the tissue surface in the magnet bore to 16 spectrometers, each containing two optical gratings optimized for the near infrared wavelength range. High sensitivity, cooled charge coupled devices connected to each spectrograph provide detection of the spectrally resolved signal, with exposure tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
138
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 166 publications
(140 citation statements)
references
References 30 publications
1
138
0
Order By: Relevance
“…Take the Born Ratio of the data (fluorescence divided by transmittance) for each source-detector position and multiply with a forward model simulation of transmittance based on the finite-element animal mesh for uniform optical properties. This is done to mitigate errors associated with source-or detector-tissue coupling 21 , to calibrate the data to the model 22 , and to adjust data for other aspects of model-data mismatch 23,24 . 7.…”
Section: Image Reconstructionmentioning
confidence: 99%
“…Take the Born Ratio of the data (fluorescence divided by transmittance) for each source-detector position and multiply with a forward model simulation of transmittance based on the finite-element animal mesh for uniform optical properties. This is done to mitigate errors associated with source-or detector-tissue coupling 21 , to calibrate the data to the model 22 , and to adjust data for other aspects of model-data mismatch 23,24 . 7.…”
Section: Image Reconstructionmentioning
confidence: 99%
“…A detailed description of this instrument can be found in Davis et al 10 The imaging array used in the studies reported here consisted of 16 source/detector fibers surrounding a cylindrical tissue phantom as shown in Fig. 3.…”
Section: B Experimental Systemmentioning
confidence: 99%
“…[1][2][3][4] Broad efforts to develop these strategies for tissue diagnosis and characterization have included exploiting novel biochemical probes, engineering new detection techniques, improving image recovery methods, [5][6][7][8] and coupling luminescence detectors to standard imaging systems. 9,10 Extracting meaningful spectroscopic measurements or accurate images of the luminescent activity in tissue requires accurate light transport modeling, which, through substantial growth since the early 1990s, 11 has become fairly mature field of research. While fluorescence molecular imaging and spectroscopy systems for use in small animals 4,10,[12][13][14][15][16] have evolved to the point of commercial availability and clinical trials in humans are underway, 17 some of the more subtle complexities of the signal acquisition remain to be examined.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In molecular systems nonlinear optical spectroscopy is utilized to study transient molecular phenomena [1][2][3][4][5][6][7][8] and local interactions [9,10], for driving [11] and coherent control [12][13][14], and for molecular imaging [15,16]. Theory of nonlinear optical spectroscopy was developed [17,18] and successfully utilized in numerous studies [19][20][21][22][23][24][25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%